Sosialisasi Pencegahan Kekerasan Berbasis Gender Melalui Media Banner di UIN K.H. Adurrahman Wahid Pekalongan - Durrotul Hikmah Yuliangsih; Rofiqotul Aini (KHIDMAH: Jurnal Pengabdian Masyarakat, 2023)
This service training aims to introduce forms of sexual violence that occur in the campus area in order to prevent this from happening. Service activities carried out by gender ambassadors under the auspices of the Center for Gender and Children Studies in the form of distributing posters which took place face-to-face at K.H Abdurrahman Wahid Pekalongan State Islamic University, the target of this activity were the Deans of the Faculty and the entire community of K.H. Abdurrahman Wahid Pekalongan State Islamic University . The implementation method in this socialization activity uses the visit method, the debriefing method, and the delivery method. The results of this activity are increasing the attention of the campus community about gender issues and succeeding in introducing services available at PSGA, so that the campus community becomes more courageous to speak up when experiencing or seeing gender-related problems to the authorities without fear. and without feeling alone. This is proven after this activity the campus community has an interest in gender issues and when there are open activities on campus more and more people participate.